2019
DOI: 10.5216/ref.v16i0.45958
|View full text |Cite
|
Sign up to set email alerts
|

Acompanhamento Farmacoterapêutico Em Unidade De Internação Pós-Transplante: Descrição E Análise.

Abstract: Objetivou-se descrever e analisar o acompanhamento farmacoterapeutico (AFT) dos pacientes transplantados em um hospital universitário do Ceará. Foram analisados os AFT dos pacientes transplantados e os registros do serviço de farmácia clínica, onde foi observado que o AFT do paciente transplantado era composto pelo monitoramento das terapias imunossupressoras, profilaxias, tratamento de comorbidades e acompanhamento de exames laboratoriais. Em 170 AFT, foram detectados 581 problemas relacionados a medicamentos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…In 2019, Oliveira et al 25 also showed that problems related to "necessary medication not prescribed" are most prevalent (26.2%), followed by underdosing (14.3%) and overdose (13.4%). Such studies corroborate the values obtained by this study, in which the most prevalent DPR were "necessary medication not prescribed" (20.11%, n = 73), followed by inadequate infusion time and dilution (13.50%, n = 49) and overdose (12.95%, n = 47).…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, Oliveira et al 25 also showed that problems related to "necessary medication not prescribed" are most prevalent (26.2%), followed by underdosing (14.3%) and overdose (13.4%). Such studies corroborate the values obtained by this study, in which the most prevalent DPR were "necessary medication not prescribed" (20.11%, n = 73), followed by inadequate infusion time and dilution (13.50%, n = 49) and overdose (12.95%, n = 47).…”
Section: Discussionmentioning
confidence: 99%
“…The fundamental principles of clinical pharmacist are the prescriptions evaluation, medicine dosages, form of administration, storage of medications, adherence and rational use of medications, and adverse reactions with medications and/or foods (Nicoletti & Ito, 2018). This service should be performed with the collaboration of the patient and by other health professionals, being continuous and documented, in order to improve the patient's quality of life (Oliveira et al, 2019;Costa & Klock, 2019).…”
Section: Introductionmentioning
confidence: 99%